2008
DOI: 10.1116/1.2897316
|View full text |Cite
|
Sign up to set email alerts
|

Study of tungsten oxidation in O2∕H2∕N2 downstream plasma

Abstract: Articles you may be interested inStudy on the oxidation and reduction of tungsten surface for sub-50nm patterning process J. Vac. Sci. Technol. A 30, 061305 (2012); 10.1116/1.4758790 Effect of Cu contamination on recombination of O atoms on a plasma-oxidized silicon surfaceThe surface oxidation of tungsten is a serious issue in plasma processing of advanced integrated-circuit devices where tungsten is being used as a gate electrode. In this article, we study tungsten oxidation in O 2 / H 2 / N 2 downstream pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…3(b)). 13,14,16,17 Tungsten oxidation (WO 3 ) at reduced pressures increases exponentially with a small addition of oxygen in the temperature range of 20 C to 300 C, and rapidly increases above 300 C. 16,17 At higher powers (several mW), the microcantilevers go through Deflection peaks observed at the beginning and end of the laser heating pulse are attributed to ablation backpressure from the heating laser. [12][13][14][15] an irreversible bending transition similar to that observed for gold (Au) coated silicon nitride microcantilevers, and the W film becomes optically transparent or completely ablated.…”
mentioning
confidence: 95%
“…3(b)). 13,14,16,17 Tungsten oxidation (WO 3 ) at reduced pressures increases exponentially with a small addition of oxygen in the temperature range of 20 C to 300 C, and rapidly increases above 300 C. 16,17 At higher powers (several mW), the microcantilevers go through Deflection peaks observed at the beginning and end of the laser heating pulse are attributed to ablation backpressure from the heating laser. [12][13][14][15] an irreversible bending transition similar to that observed for gold (Au) coated silicon nitride microcantilevers, and the W film becomes optically transparent or completely ablated.…”
mentioning
confidence: 95%
“…2. The increase in W peak height after annealing in hydrogen due to the removal of oxygen, has also been observed by other researchers [16], [17]. The RUMP simulation of the sample annealed at 700 ºC indicated that (1), (2) and (3) …”
Section: Rutherford Backscattering Spectrometry (Rbs)mentioning
confidence: 56%
“…This W 4f 7/2 from the substrate at 31.6 eV will be set as the binding energy reference in the following. The presence of well-defined doublets located at 36.1 and 38.2 eV along with a broad feature at higher binding energy typical of the W 6+ state in oxides is consistent with an oxidized TiW surface. , In Figure b, Ti 2p 3/2 and Ti 2p 1/2 with binding energies of 458.6 and 464.4 eV, respectively, correspond to Ti 4+ state in oxides, whereas two other peaks observed at 453.7 and 459.7 eV correspond to metallic Ti 0 in TiW. , The area ratio of W/Ti corrected by photoionization cross section is 2.4: the TiW substrate contains more W than Ti. In Figure a, O 1s spectra show two peaks located at 530.5 and 531.3 eV, which are identified as contributions from metal oxides (labeled metal–O) and from metal hydroxides (labeled metal–OH), respectively.…”
Section: Resultsmentioning
confidence: 99%